2013
DOI: 10.1136/jnnp-2012-303826
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral stereotactic anterior capsulotomy for obsessive-compulsive disorder: long-term follow-up

Abstract: Anterior capsulotomy is an effective and safe technique for the treatment of severe refractory OCD in patients who have no other alternative to improve their symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 30 publications
2
56
1
1
Order By: Relevance
“…38 For patients with OCD who underwent AC, one study found no difference in the presurgery YBOCS scores between patients who responded to surgery and nonresponders. 8 In contrast, the average presurgery YBOCS scores of nonresponders (YBOCS score < 35% improvement) at the Karolinska Institute was 35 (SD 3), compared with 32 (SD 3) for patients who had a clinically significant response (p = 0.02), suggesting that OCD symptom severity may have a negative predictive value for treatment response. 37 Moreover, worse OCD severity is also associated with a higher number of comorbidities, particularly generalized anxiety disorder and agoraphobia.…”
Section: Severity Of Ocdmentioning
confidence: 71%
See 3 more Smart Citations
“…38 For patients with OCD who underwent AC, one study found no difference in the presurgery YBOCS scores between patients who responded to surgery and nonresponders. 8 In contrast, the average presurgery YBOCS scores of nonresponders (YBOCS score < 35% improvement) at the Karolinska Institute was 35 (SD 3), compared with 32 (SD 3) for patients who had a clinically significant response (p = 0.02), suggesting that OCD symptom severity may have a negative predictive value for treatment response. 37 Moreover, worse OCD severity is also associated with a higher number of comorbidities, particularly generalized anxiety disorder and agoraphobia.…”
Section: Severity Of Ocdmentioning
confidence: 71%
“…Of these, 10 studies included 108 patients with capsulotomy 5,7,8,17,23,26,28,32,37,41 and 10 included 62 patients who underwent DBS. 1,9,13,14,18,19,21,35,36,47 Table 1 (AC) and Table 2 (DBS) present details of the number of patients in each study, age at surgery, length of follow-up, details of the surgical procedures, and pre-and postoperative YBOCS scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Объем, локализация и МР-харак-теристики очагов, получаемых при ультразвуковой де-струкции, совпадают с таковыми при радиочастотной термоабляции [22,36,37]. При этом эффективность уль-тразвуковой деструкции представляется сопоставимой с эффективностью радиочастотной термоабляции, а также стимуляции глубинных структур [18,19,22,32,35,[38][39][40][41][42][43][44]. Из всех деструктивных методик ФУЗ представляется наи-более оптимальной, так как эта процедура, в отличие от прямой стереотаксической радиочастотной абляции, ис-ключает риски внутримозговых кровоизлияний, инфици-рования и др., и по сравнению с радиохирургическим ле-чением характеризуется возможностью физиологической верификации, предсказуемостью результата и быстрым развитием эффекта [19,[45][46][47].…”
Section: обзорыunclassified